Hidup Damai Dengan Alam Perspektif Umat Buddha Vihara Mahavira Graha Semarang - Azizah, Miftakhul; Muchlizun, Moch.; Abror, Muhammad Faisal; Hidayatullah, Ahmad Fauzan (Universitas Islam Negeri Raden Intan Lampung, 2022)
Every religion must have its concept of living in peace with nature, including Buddhism with its theological teachings. Buddhism is known as a religion that highly upholds a sense of savage love for the preservation of nature. Buddhism views that there is a relationship between one's morality and nature preservation because events that occur in nature influence each other. This study aims to determine the perspective of the Buddhist Vihara Mahavira Graha Semarang about living in peace with nature. The research data was obtained by conducting in-depth interviews with Suhu Chuan Ling, then analyzed by descriptive-analytic. The results of this study are (1) Buddhism has a concern for the surrounding environment to preserve the environment: (2) Living in peace with nature is closely related to the vegetarian lifestyle as the Buddhists in this monastery who adhere to the Mahayana sect; (3) Buddhism understands that nature is impermanent, so humans need to accept the nature possessed by nature so that the benefits that humans receive also increase.